STOCHASTIC RELIABILITY MODEL OF MODERNIZED DIESEL LOCOMOTIVE (Perner's Contacts, 2009)
The modernization of diesel locomotives is often used method of powered vehicles fleet restoration in present. The issues associated with this process are related with achievement of expected higher level of reliability and maintainability after modernization realization. This problem solution is content of the paper.
Keywords: powered vehicles; modernization; reliability; maintainability